NEGOSIASI DALAM DIPLOMASI EKONOMI: DIPLOMASI INDONESIA-PT FREEPORT 2014-2018 - aulia, maharani versyah (Global and Policy Journal of International Relations, 2023)
Indonesia as one of the countries with potential mining resources has attracted foreign investors, one of which is PT. Freeport Indonesia (PTFI). The cooperation between PTFI and Indonesia has been ongoing since 1967. The relationship between PTFI and Indonesia agreed through the Work Contract was considered unbalanced and more detrimental to Indonesia, so the Indonesian government issued Mining Law no. 4 of 2009. The existence of the Mining Law requires renegotiation between Freeport and Indonesia. The negotiations took a long time until finally in 2018 an agreement was reached, one of which was regarding the divestment of 51% shares. In this negotiation process, Indonesia is said to be successful because it has obtained the desired results and made Freeport agree. Thus, this study aims to determine the success factors of negotiations conducted by Indonesia-PT. Freeport seen from the lens of economic diplomacy. The results showed that the success factors of negotiations in Indonesia's economic diplomacy consisted of systemic factors, consensus, and ideas.DOI: https://doi.org/10.33005/jgp.v11i01.3848